REMOVED: Adaptive multiclass support vector machine for multimodal data analysis. (October 2017) - Zhang, Xin; Zhang, Xiu
Abstract : The Publisher regrets that this article has been temporarily removed. A replacement will appear as soon as possible in which the reason for the removal of the article will be specified, or the article will be reinstated. The full Elsevier Policy on Article Withdrawal can be found athttp://www.elsevier.com/locate/withdrawalpolicy .